From oncogene to network addiction: the new frontier of cancer genomics and therapeutics. (August 2008) - Tonon, Giovanni
Recent advances in genomic analysis have provided a comprehensive view of the genetic and epigenetic changes present in cancer cells. While therapies targeting genes causally linked to carcinogenesis have been successful in a subset of tumor types, the hope for treatments tailored on patient genomic profiles seems, for most cancers, still elusive. Cancer genes belong to two clearly defined groups. The first subset of genes is frequently mutated across samples and tumor types, and includes well-studied oncogenes and tumor suppressor genes, such as members of the RAS, AKT and TP53 families, whose direct targeting has so far been largely disappointing. In the other group, the vast majority of putative cancer genes emerging from sequencing and genomic studies show a low incidence (5% or less). The possibility of finding novel selective drugs against such a high number of gene products seems daunting. However, recent genomic and proteomic findings, as well as novel frameworks arising from systems biology approaches, suggest that this apparent discordance may converge towards a more satisfying model. It seems that genetic lesions in cancer tend to cluster around certain pathways, suggesting that the concept of ''network addiction'', rather than ''oncogene addiction'', would recapitulate more closely what is happening during tumor development and after exposure to therapeutic agents. This new perspective, arising from genomic and systems biology studies, will likely provide a valuable frame for the design of the cancer drugs of the future.